A high-strength, anti-seepage and anti-cracking composite concrete and preparation method thereof
By optimizing the component distribution ratio in high-strength concrete and adding permeable crystalline waterproofing agent and polyvinylidene chloride fiber, the problem of insufficient anti-seepage and cracking performance of high-strength concrete in humid environments is solved, and higher strength and anti-seepage and cracking performance are achieved.
Patent Information
- Application Number
- CN202411977838.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
In humid environments, high-strength concrete causes expansion stress to form inside due to the hydration reaction of unhydrated cement particles, which in turn affects its anti-seepage and crack resistance.
Improve the permeability and crack resistance of concrete by optimizing the component distribution ratio and adding a variety of functional materials, such as permeable crystalline waterproofing agents and polyvinylidene chloride fibers. Permeable crystalline waterproofing agents include active substances and polyhydroxy organic complexes, which can enhance the compactness and impermeability of concrete, while polyvinylidene chloride fibers can control the development of microscopic cracks and improve tensile strength and toughness.
The number, width and depth of concrete cracks are significantly reduced, the strength and impermeability and crack resistance of concrete are improved, making it more stable in humid environments.
Smart Images

Figure BDA0005220844690000051 
Figure BDA0005220844690000061 
Figure BDA0005220844690000062
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete technology, and in particular to a high-strength, impermeability and crack-resistant composite concrete and a preparation method thereof. Background Art
[0002] As an emerging building material, high-strength concrete has been widely used in high-rise building structures, long-span bridge structures and specific special structures due to its excellent compressive strength, excellent deformation resistance, high density and low porosity. As an economical and efficient civil engineering material, high-strength concrete has many advantages. However, in practical applications, due to its high proportion of cementitious materials, it contains a large amount of unhydrated cement particles, which can account for 40% to 70% of the total cement. In a humid environment, once high-strength concrete absorbs water, these unhydrated cements will continue to undergo hydration reactions, and the volume of the generated hydration products will be significantly larger than the original volume of the unhydrated cement. As the hydration products gradually fill the internal voids of the concrete, if the hydration reaction continues, the product volume may exceed the volume limit of the internal voids of the concrete, thereby forming expansion stress inside the concrete, and eventually leading to a large number of microcracks inside the concrete, which in turn affects its impermeability and crack resistance. Summary of the invention
[0003] In order to solve at least one of the above technical problems, the present application provides a high-strength, impermeability and crack-resistant composite concrete and a preparation method thereof.
[0004] On the one hand, the present application provides a high-strength, anti-seepage and anti-cracking composite concrete, comprising the following raw materials in parts by weight: 130-160 parts of cement, 77-85 parts of ultrafine fly ash, 25-38 parts of slag powder, 225-330 parts of sand, 310-400 parts of gravel, 5-10 parts of penetrating crystalline waterproofing agent, 9-18 parts of polyvinylidene chloride fiber, 1-2 parts of admixture, and 80-92 parts of water.
[0005] By adopting the above technical solution, the present application aims to improve the impermeability and crack resistance of concrete by optimizing the component ratio and adding a variety of functional materials. The addition of polyvinylidene chloride fiber (can effectively control the development of micro cracks in the concrete plastic stage and after hardening, improve the tensile strength and toughness of concrete, and reduce cracking. The addition of penetrating crystalline waterproofing agent can effectively enhance the impermeability of concrete.
[0006] Optionally, the penetrating crystalline waterproofing agent includes a polyhydroxy organic complex, an active substance and a polycarboxylate water-reducing agent.
[0007] By adopting the above technical solution, the penetrating crystalline waterproofing agent of the present application includes active substances and polyhydroxy organic complexes. The active substances can adhere to the surface of cement particles, so that the cement can be better dispersed and release more free water. As a result, the water consumption per unit volume of the concrete mixture is reduced, the porosity inside the concrete is reduced, and the generated hydration products are closely arranged and more dense. This greatly reduces the number, width and depth of concrete cracks, and improves the strength and anti-seepage and anti-cracking properties of the concrete.
[0008] Optionally, the weight ratio of the polyhydroxy organic complex to the active substance is (8-10): (10-15).
[0009] Optionally, the polyhydroxy organic complex is one of tartaric acid and catechol.
[0010] Optionally, the active substance includes sodium citrate, slaked lime, sodium methyl silicate and sodium silicate in a weight ratio of (3-6):(5-8):1:1.
[0011] Optionally, the weight ratio of the penetrating crystalline waterproofing agent to the polyvinylidene chloride fiber is 1:(1.5-2.1).
[0012] Optionally, the weight ratio of the penetrating crystalline waterproofing agent to the polyvinylidene chloride fiber is 1:1.8.
[0013] Optionally, the total weight of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber accounts for (1.7-2.8)% of the total weight of the high-strength anti-seepage and anti-cracking composite concrete raw materials.
[0014] By adopting the above technical solution, the present application defines the weight ratio of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber and the proportion in the concrete, and the penetrating crystalline waterproofing agent can effectively improve the density and impermeability of the concrete. The polyvinylidene chloride fiber can enhance the tensile strength and toughness of the concrete, and control the crack expansion in the plastic stage and after hardening. Through the appropriate proportion, the waterproofing agent and the fiber can complement each other and jointly improve the comprehensive performance of the concrete.
[0015] Optionally, the admixture is a polycarboxylate water reducer.
[0016] In a second aspect, the present application provides a method for preparing the above-mentioned high-strength, impermeability and crack-resistant composite concrete, comprising the following steps: S1. Mix cement, ultrafine fly ash, slag powder, sand and crushed stone, and stir for 3-5 minutes to obtain a dry premix; S2. Mix the admixture, the penetrating crystalline waterproofing agent, the polyvinylidene chloride fiber, water and the dry premix, and stir for 10-15 minutes to obtain a high-strength, anti-seepage and anti-cracking composite concrete.
[0017] By adopting the above technical scheme, the preparation method of the high-strength anti-seepage and anti-cracking composite concrete of the present application is simple and easy to operate, and the prepared concrete has good anti-seepage and anti-cracking properties.
[0018] In summary, the present invention includes at least one of the following beneficial technical effects: 1. This application aims to improve the impermeability and crack resistance of concrete by optimizing the component ratio and adding a variety of functional materials. The addition of polyvinylidene chloride fiber (can effectively control the development of micro cracks in the concrete plastic stage and after hardening, improve the tensile strength and toughness of concrete, and reduce cracking. The addition of penetrating crystalline waterproofing agent can effectively enhance the impermeability of concrete.
[0019] 2. The penetrating crystalline waterproofing agent of the present application includes active substances and polyhydroxy organic complexes. The active substances can adhere to the surface of cement particles, so that the cement can be better dispersed and release more free water. As a result, the water consumption per unit volume of the concrete mixture is reduced, the porosity inside the concrete is reduced, and the generated hydration products are closely arranged and more dense. This greatly reduces the number, width and depth of concrete cracks, and improves the strength and anti-seepage and anti-cracking properties of the concrete.
[0020] 3. This application defines the weight ratio of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber and the proportion in the concrete. The penetrating crystalline waterproofing agent can effectively improve the density and impermeability of the concrete. The polyvinylidene chloride fiber can enhance the tensile strength and toughness of the concrete and control the crack expansion in the plastic stage and after hardening. Through the appropriate proportion, the waterproofing agent and the fiber can complement each other and jointly improve the comprehensive performance of the concrete.
[0021] 4. The preparation method of the high-strength, impermeability and crack resistance composite concrete of the present application is simple and easy to operate, and the prepared concrete has good impermeability and crack resistance. DETAILED DESCRIPTION
[0022] The present application is further described in detail below in conjunction with embodiments.
[0023] The present application provides a high-strength, anti-seepage and anti-cracking composite concrete, which includes the following raw materials in parts by weight: 130-160 parts of cement, 77-85 parts of ultrafine fly ash, 25-38 parts of slag powder, 225-330 parts of sand, 310-400 parts of crushed stone, 5-10 parts of penetrating crystalline waterproofing agent, 9-18 parts of polyvinylidene chloride fiber, 1-2 parts of admixture, and 80-92 parts of water.
[0024] The present application provides a method for preparing the above-mentioned high-strength, impermeability and crack-resistant composite concrete, comprising the following steps: S1. Mix cement, ultrafine fly ash, slag powder, sand and crushed stone, and stir for 3-5 minutes to obtain a dry premix; S2. Mix the admixture, the penetrating crystalline waterproofing agent, the polyvinylidene chloride fiber, water and the dry premix, and stir for 10-15 minutes to obtain a high-strength, anti-seepage and anti-cracking composite concrete.
[0025] This application aims to improve the impermeability and crack resistance of concrete by optimizing the component ratio and adding a variety of functional materials. The addition of polyvinylidene chloride fiber (can effectively control the development of micro cracks in the concrete plastic stage and after hardening, improve the tensile strength and toughness of concrete, and reduce cracking. The addition of penetrating crystalline waterproofing agent can effectively enhance the impermeability of concrete.
[0026] The preparation method of the high-strength anti-seepage and anti-cracking composite concrete of the present invention is simple and easy to operate, and the prepared concrete has good anti-seepage and anti-cracking properties. Specific embodiments
[0027] Example 1 The present embodiment provides a high-strength, anti-seepage and anti-cracking composite concrete, comprising the following raw materials in parts by weight: 130 parts of cement, 77 parts of ultrafine fly ash, 25 parts of slag powder, 225 parts of sand, 310 parts of crushed stone, 7 parts of penetrating crystalline waterproofing agent, 14 parts of polyvinylidene chloride fiber, 1 part of admixture, and 80 parts of water.
[0028] Among them, the penetrating crystallization waterproofing agent is a polyhydroxy organic complex, an active substance and a polycarboxylic acid water reducer in a weight ratio of 8:10; the polyhydroxy organic complex is tartaric acid; the active substance includes sodium citrate, slaked lime, sodium methyl silicate and sodium silicate in a weight ratio of 3:5:1:1, and the admixture is a polycarboxylic acid water reducer.
[0029] The preparation method of the high-strength anti-seepage and anti-cracking composite concrete in this embodiment comprises the following steps: S1. Mix cement, ultrafine fly ash, slag powder, sand and gravel, and stir for 4 minutes to obtain a dry premix; S2. Mix the admixture, the penetrating crystalline waterproofing agent, the polyvinylidene chloride fiber, water and the dry premix, and stir for 12 minutes to obtain a high-strength, anti-seepage and anti-cracking composite concrete.
[0030] Embodiment 2-4 Example 2 The difference between this embodiment and embodiment 1 is that when preparing high-strength anti-seepage and anti-cracking composite concrete, the total weight of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber is 21 parts, and the weight ratio of the penetrating crystalline waterproofing agent to the polyvinylidene chloride fiber is 1:1.5.
[0031] Example 3 The difference between this embodiment and embodiment 1 is that when preparing high-strength anti-seepage and anti-cracking composite concrete, the total weight of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber is 25 parts, and the weight ratio of the penetrating crystalline waterproofing agent to the polyvinylidene chloride fiber is 1.:1.8.
[0032] Example 4 The difference between this embodiment and embodiment 1 is that when preparing high-strength anti-seepage and anti-cracking composite concrete, the total weight of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber is 25 parts, and the weight ratio of the penetrating crystalline waterproofing agent to the polyvinylidene chloride fiber is 1:2.1.
[0033] Comparative Examples 1-3 Comparative Example 1 The difference between this comparative example and Example 1 is that no polyvinylidene chloride fiber is added when preparing the high-strength, impermeability and crack resistance composite concrete.
[0034] Comparative Example 2 The difference between this comparative example and Example 1 is that no penetrating crystalline waterproofing agent is added when preparing the high-strength anti-seepage and anti-cracking composite concrete.
[0035] Comparative Example 3 The difference between this comparative example and Example 1 is that when preparing the high-strength anti-seepage and anti-cracking composite concrete, no penetrating crystalline waterproofing agent and polyvinylidene chloride fiber are added.
[0036] Experimental testing: Compressive strength test: According to GB / T 50081-2002, the compressive strength test of the high-strength, impermeable and crack-resistant composite concrete specimens prepared in the examples and comparative examples of the present application was carried out, and the 28d compressive strength F1 of each specimen was measured; Crack resistance test: According to JGJ / T 193-2009, the crack resistance test was carried out on the specimens of the high-strength, impermeability and crack-resistant composite concrete prepared in the examples and comparative examples of the present application; Anti-seepage performance test: According to the water seepage height method in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the water seepage height of each test block was measured three months later.
[0037] The experimental test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.
[0038] Table 1 Experimental test results of Examples 1-4 and Comparative Examples 1-3 Example <![CDATA[F1(MPa)]]> Crack resistance grade Water seepage height (mm) Example 1 78.6 L-IV 9.6 Example 2 75.1 L-IV 10.7 Example 3 82.7 LV 8.4 Example 4 80.2 L-IV 9.0 Comparative Example 1 61.8 L-III 14.9 Comparative Example 2 67.4 L-III 17.4 Comparative Example 3 54.2 L-II 20.5 Result analysis: The difference between Example 2-4 and Example 1 is that when preparing high-strength anti-seepage and anti-cracking composite concrete, the total weight of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber is 21 parts, and the weight ratio of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber is different. Combined with the experimental test results of Table 1, it can be seen that when the weight ratio of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber is 1:1.8, the obtained high-strength anti-seepage and anti-cracking composite concrete has a higher compressive strength, better crack resistance, and better anti-seepage ability. The difference between Comparative Example 1 and Example 1 is that when preparing high-strength anti-seepage and anti-cracking composite concrete, polyvinylidene chloride fiber is not added. The difference between Comparative Example 2 and Example 1 is that when preparing high-strength anti-seepage and anti-cracking composite concrete, no penetrating crystalline waterproofing agent is added. The difference between Comparative Example 3 and Example 1 is that when preparing high-strength anti-seepage and anti-cracking composite concrete, no penetrating crystalline waterproofing agent and polyvinylidene chloride fiber are added. Combined with the experimental test results in Table 1, it can be seen that when preparing high-strength anti-seepage and anti-cracking composite concrete, the compound use of penetrating crystalline waterproofing agent and polyvinylidene chloride fiber can better improve the comprehensive performance of the obtained high-strength anti-seepage and anti-cracking composite concrete.
[0039] Embodiment 5-6 Example 5 The difference between Example 5-6 and Example 3 is that the weight percentages of some components are changed when preparing the high-strength, impermeability-resistant and crack-resistant composite concrete. See Table 2 for the differences.
[0040] Table 2 Differences between Examples 5-6 and Example 3 The experimental test results of Examples 5-6 are shown in Table 3.
[0041] Table 3 Experimental test results of Examples 5-6 Result analysis: The difference between Example 5-6 and Example 3 is that when preparing high-strength, anti-seepage and anti-cracking composite concrete, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that when preparing high-strength, anti-seepage and anti-cracking composite concrete, the high-strength, anti-seepage and anti-cracking composite concrete prepared in Example 5 has better comprehensive performance.
[0042] Embodiment 7-9 The difference between Example 7-9 and Example 5 is that when preparing high-strength anti-seepage and anti-cracking composite concrete, on the premise that the weight ratio of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber is 1:1.8, the proportion of the total weight of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber in the total weight of the raw materials of the high-strength anti-seepage and anti-cracking composite concrete is changed, and a better weight proportion is selected.
[0043] In Example 5, the total weight of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber is 21 parts, and the total weight of the high-strength anti-seepage and anti-cracking composite concrete raw materials is 1002 parts.
[0044] Therefore, it is not difficult to conclude that in Example 5, the proportion of the penetrating crystalline waterproofing agent (called variable 1) and the polyvinylidene chloride fiber (called variable 2) in the total weight of the high-strength, impermeable and crack-resistant composite concrete raw materials (called the matrix) is 2.10%.
[0045] The differences between Examples 7-9 and Example 5 are shown in Table 4.
[0046] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.
[0047] Table 4 Differences between Examples 7-9 and Example 5 The experimental test results of Examples 7-9 are shown in Table 5.
[0048] Table 5 Experimental test results of Examples 7-9 Result analysis: The difference between Example 7-9 and Example 5 is that when preparing high-strength anti-seepage and anti-cracking composite concrete, when the proportion of the penetrating crystalline waterproofing agent (called variable 1) and the polyvinylidene chloride fiber (called variable 2) in the total weight of the raw materials of the high-strength anti-seepage and anti-cracking composite concrete (called the matrix) is between (1.7-2.8)%, the comprehensive performance of the obtained high-strength anti-seepage and anti-cracking composite concrete is better. When the proportion of the penetrating crystalline waterproofing agent (called variable 1) and the polyvinylidene chloride fiber (called variable 2) in the high-strength anti-seepage and anti-cracking composite concrete (called the matrix) is 2.1%, the comprehensive performance of the obtained high-strength anti-seepage and anti-cracking composite concrete is better.
[0049] Example 10 The difference between Example 10 and Example 5 is that the penetrating crystallization type waterproofing agent is a polyhydroxy organic complex, an active substance and a polycarboxylic acid water reducer in a weight ratio of 9:12; the polyhydroxy organic complex is tartaric acid; and the active substance includes sodium citrate, slaked lime, sodium methyl silicate and sodium silicate in a weight ratio of 4:7:1:1.
[0050] Embodiment 11 The difference between Example 11 and Example 5 is that the penetrating crystallization type waterproofing agent is a polyhydroxy organic complex, an active substance and a polycarboxylic acid water reducer in a weight ratio of 10:15; the polyhydroxy organic complex is tartaric acid; and the active substance includes sodium citrate, slaked lime, sodium methyl silicate and sodium silicate in a weight ratio of 6:8:1:1.
[0051] The experimental test results of Examples 10-11 are shown in Table 6.
[0052] Table 6 Experimental test results of Examples 10-11 Result analysis: The difference between Examples 7-9 and Example 5 is that when preparing high-strength, anti-seepage and anti-cracking composite concrete, the composition and proportion of the penetrating crystalline waterproofing agent are different. Combined with the experimental test results in Table 6, it can be seen that when preparing high-strength, anti-seepage and anti-cracking composite concrete, the high-strength, anti-seepage and anti-cracking composite concrete prepared in Example 10 has better comprehensive performance.
[0053] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A high-strength, impermeability and crack-resistant composite concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 130-160 parts of cement, 77-85 parts of ultrafine fly ash, 25-38 parts of slag powder, 225-330 parts of sand, 310-400 parts of crushed stone, 5-10 parts of penetrating crystalline waterproofing agent, 9-18 parts of polyvinylidene chloride fiber, 1-2 parts of admixture and 80-92 parts of water.
2. The high-strength, impermeability and crack-resistant composite concrete according to claim 1, characterized in that: The penetrating crystallization waterproofing agent comprises a polyhydroxy organic complex, an active substance and a polycarboxylic acid water-reducing agent.
3. The high-strength, impermeability and crack-resistant composite concrete according to claim 1, characterized in that: The weight ratio of the polyhydroxy organic complex to the active substance is (8-10): (10-15).
4. The high-strength, impermeability and crack-resistant composite concrete according to claim 1, characterized in that: The polyhydroxy organic complex is one of tartaric acid and catechol.
5. The high-strength, impermeability and crack-resistant composite concrete according to claim 1, characterized in that: The active substance includes sodium citrate, slaked lime, sodium methyl silicate and sodium silicate in a weight ratio of (3-6):(5-8):1:
1.
6. The high-strength, impermeability and crack-resistant composite concrete according to claim 1, characterized in that: The weight ratio of the penetrating crystalline waterproofing agent to the polyvinylidene chloride fiber is 1:(1.5-2.1).
7. The high-strength, impermeability and crack-resistant composite concrete according to claim 6, characterized in that: The weight ratio of the penetrating crystalline waterproofing agent to the polyvinylidene chloride fiber is 1:1.
8.
8. The high-strength, impermeability and crack-resistant composite concrete according to claim 1, characterized in that: The total weight of the penetrating crystalline waterproofing agent and the polyvinylidene chloride fiber accounts for (1.7-2.8)% of the total weight of the high-strength anti-seepage and anti-cracking composite concrete raw materials.
9. The high-strength, impermeability and crack-resistant composite concrete according to claim 1, characterized in that: The admixture is a polycarboxylate water reducer.
10. A method for preparing the high-strength, impermeability-resistant and crack-resistant composite concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Mix cement, ultrafine fly ash, slag powder, sand and crushed stone, and stir for 3-5 minutes to obtain a dry premix; S2. Mix the admixture, the penetrating crystalline waterproofing agent, the polyvinylidene chloride fiber, water and the dry premix, and stir for 10-15 minutes to obtain a high-strength, anti-seepage and anti-cracking composite concrete.